Untangling trade and technology: Evidence from local labor markets - David H. Autor; David Dorn; Gordon H. Hanson (Institute for the Study of Labor (IZA), 2013)
We juxtapose the effects of trade and technology on employment in U.S. local labor markets between 1990 and 2007. Labor markets whose initial industry composition exposes them to rising Chinese import competition experience significant falls in employment, particularly in manufacturing and among non-college workers. Labor markets susceptible to computerization due to specialization in routine task-intensive activities experience significant occupational polarization within manufacturing and non-manufacturing but no net employment decline. Trade impacts rise in the 2000s as imports accelerate, while the effect of technology appears to shift from automation of production activities in manufacturing towards computerization of information-processing tasks in non-manufacturing.
Keywords: F16; J21; J23; O33; 330; technological change; trade flows; import competition; skill demand; job tasks; local labor markets